(untitled) (Khairulummah, 2022)
دكتور/حبيب نواز، رئيس قسم اللغات الباكستانية، الجامعة الوطنية للغات الحديثة، إسلام آباد Hasan Tahir Rasul Researcher In Majlis Ul Buhoos Al Islami for Spicialisation in Hadees & Arabic Literature, Rawal pindi Pak. Abstract The erudite scholarship of Imam Abul Hasan Ali Nadwi Rahimahullah became world-renowned in his own lifetime, and unsurprisingly so - being one of the key scholars of the twentieth century who redrew the attention of the Ummah towards seeking Arabic literature from sources more Islamic than sufficing on the likes of poets such as Imru’ul-Qays which had dominated Arabic literature studies for centuries. Furthermore, these scholars also re-emphasised the fact that the Qur’aan Majeed and the Ahaadeeth of Rasulullah (Sallallahu Alayhi Wa Sallam) were both the fundamental and greatest sources of Arabic literature, and also provided the poetry of Hassan bin Thabit (Radhiyallahu Anhu) as evidence that Rasulullah (Sallallahu Alayhi Wa Sallam) himself promoted excellence in this field. Thus, in this paper we have mentioned some of the contributions of Imam Abul Hasan Ali Nadwi in the field of Arabic literature and more specifically Islamic Arabic literature; thereby attempting to prove that Imam Abul Hasan Rahimahullah was from the first people to recall towards Islamic Arabic literature, providing testimonies of leading scholars of the field to further cement this claim.